Case Report: Contribution of [18F]FET PET in differential diagnosis between radionecrosis and progression in metastasis—reproducibility and superiority of dynamic acquisitions - Callaud, Aurélien; Dupont, Anne-Claire; By, Marie-Agnes; Zemmoura, Ilyess; Santiago-Ribeiro, Maria-Joao (Frontiers in Nuclear Medicine, 2024)
We present the case of a 67-year-old woman with metastatic invasive ductal carcinoma of the left breast, in whom a follow-up MRI, three months after encephalic radiotherapy, revealed a significant increase in the size of two brain metastases, potentially indicating progressive disease within the radiation field. Subsequent 18FFDG and 18FFET PET scans were performed, to distinguishing radionecrosis from tumor progression. Despite dynamic 18FFET TAC against progression, the exceeding of cutoff TBR mean of 1.9 and interdisciplinary considerations led to the resection of one lesion. Histopathology revealed necrosis due to radiotherapy, without viable tumor proliferation. To verify radionecrosis, a second 18FFET PET was conducted, showing consistent findings. In metastasis differentiation, TBR mean cutoff of 1.9 and TAC analysis achieve 95% sensitivity and 91% specificity. Discrepancy between TAC and TBR emphasizes the need for consideration, and time delay between radiotherapy and PET may impact TBR cutoffs. Also, radiosensitivity differences suggest a lower metastasis pre-test probability of progression, and it might be why TAC analysis could be more effective in distinguishing TP from TRC in metastasis. This case demonstrates dynamic 18FFET PET's accuracy and suggests its utility for post-treatment metastasis evaluation, and further research on post-treatment delay could lead to improved dynamic 18FFET PET's performances.